The Cost of Panai' as the Marriage Requirement for the Migrant Bugis Tribe under Adat Law - Dhelima Putri Laksana; Dominikus Rato; Emi Zulaikha (Faculty of Law, University of Jember, Indonesia, 2020)
This research aims to examine the legal phenomena of the application of the panai money, the cost imposed for the migrant Bugis customary law community in Sukabumi Village, Mayangan District, Probolinggo City, East Java. In other words, Panai' money is such customary money which must be handed over in Bugis tribal marriages. The data analysis method used is descriptive qualitative. Data collection techniques using literature study, observation, interviews, and documentation. The results of this study indicate that the submission of panai money has become a tradition that originated from an ancestor that is still valid today. Due to the high panai money, however, many of the Bugis people who wander no longer use panai money, as it takes into account the weakness of their customary values, as well as the many other cultures that influence, but there are still people who still defend it because of their strong customary values ​​which they still hold even though in the migrant area. Because panai money ’is a tradition that has long been a benchmark for Bugis people, this tradition still strongly considers moral sanctions, and the avoidance of this money is responded by some people to decide to elope. Keywords: Migrant Bugis Tribe, Marriage Law, Adat Law.